Reticulocyte Hemoglobin Content (Ret He): A Simple Tool for Evaluation of Iron Status in Childhood Cancer. Issue 3 (April 2020) - Tantawy, Azza A.; Ragab, Iman A.; Ismail, Eman A.; Ebeid, Fatma S.E.; Al-Bshkar, Ramadan M.
Abstract : Background: Cancer-related anemia is a common complication of cancer and its treatment that may be mediated by nutritional deficiency or inflammatory cytokines inhibiting erythropoiesis. Aim: We evaluated the value of reticulocyte hemoglobin content (Ret He) as a marker of iron availability for erythropoiesis in childhood cancer and the impact of oral iron supplementation on hematologic parameters in patients with low Ret He. Materials and Methods: This prospective study included 100 pediatric patients with cancer on chemotherapy who were screened for the presence of anemia. Patients with anemia underwent testing for complete blood count including Ret He on Sysmex XE 2100 and assessment of reticulocyte count, serum iron, serum ferritin, transferrin saturation, total iron-binding capacity, and C-reactive protein. Patients were classified according to their level of Ret He into normal or low Ret He using a cutoff level of 28 pg. Patients with low Ret He were subjected to 6 weeks' treatment with oral ion and were followed up with complete blood count and iron profile. Results: Thirty-one (77.5%) patients had normal Ret He, and 9 (22.5%) had low Ret He. Ret He was positively correlated with red cell indices, but not with iron parameters. After oral iron supplementation, a significant increase in hemoglobin, reticulocyte count, and iron was found. Conclusions: We suggest that Ret He could be used as an easy and affordable tool for the assessment of iron deficiency anemia in childhood cancer during chemotherapy treatment. A trial of oral iron in patients with low Ret He may be useful to correct the associated anemia.